2020
DOI: 10.1111/1471-0528.16555
|View full text |Cite
|
Sign up to set email alerts
|

Planned oocyte cryopreservation (Planned OC): systematic review and meta‐analysis of cost‐efficiency and patients’ perspective

Abstract: Background Advances in vitrification techniques have enabled planned oocyte cryopreservation (‘Planned OC’). Objectives To explore the cost‐efficiency and utilisation of planned OC, as well as patients’ perspectives on the process. Search strategy A systematic search in PubMed/MEDLINE, Embase, Cochrane Database and PsychINFO, for all relevant studies published between January 2007 and December 2019. Selection criteria The protocol followed PRISMA guidelines in PECO format, and was registered with PROSPERO. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…A systematic review and meta-analysis done by Fuchs Weizman et al included 43 studies and found that planned OC is the most cost efficient at 35 years old (assuming a minimum of 60% utilization) [39,40]. Another study by Mesen et Goldman et al conducted a modeling study from a retrospective analysis of their academic infertility center data.…”
Section: Effect Of Age At Time Of Oocyte Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis done by Fuchs Weizman et al included 43 studies and found that planned OC is the most cost efficient at 35 years old (assuming a minimum of 60% utilization) [39,40]. Another study by Mesen et Goldman et al conducted a modeling study from a retrospective analysis of their academic infertility center data.…”
Section: Effect Of Age At Time Of Oocyte Retrievalmentioning
confidence: 99%
“…They also found that of the 88 patients who utilized their vitrified oocytes most returned to thaw/warm oocytes with a partner (n = 55, 62.5%) compared to donor sperm (n = 33, 37.5%) and this did not differ based on age. Fuchs Weizman et al also evaluated the utilization of oocytes after planned OC in a systematic review and found that 12.1-15% of oocytes were used 22-58 months after freezing [39].…”
Section: Utilization Of Cryopreserved Oocytesmentioning
confidence: 99%
“…Patients did not use their cryopreserved oocytes because they conceived naturally, because they did not want to be a single mother, or because of their social, personal, or professional situation (ACOG, 2014). A very low return rate makes the cost-effectiveness of the technique considerably uncertain (Ben-Rafael, 2018;Fuchs Weizman et al, 2021), and depending on the cost of EEF per cycle and the return rate, the calculated societal cost per live birth could amount to several hundreds of thousands of euros (Ben-Rafael, 2018).…”
Section: Low Return Usage Rate: Low Cost-effectivenessmentioning
confidence: 99%
“…Given that for many patients these services are not covered by insurance due to lack of a state mandate, charge data is frequently used in cost-effectiveness analyses within the reproductive endocrinology and infertility literature, which may contribute to an over-estimation of OC cost (mainly based on charge data) relative to the underestimation of OTC (cost data) [13,14,30]. Additionally, costs were estimated from published literature, which is fairly limited based on a recent review published in 2020 [15]. The institutions from which the pricing ranges were queried may also have had considerable variations.…”
Section: Discussionmentioning
confidence: 99%
“…The costs related to oocyte cryopreservation and IVF, including storage fees, thawing, fertilization, and fresh and frozen embryo transfers, were obtained from literature that obtained charges from 17 randomly selected regionally diverse clinics [13][14][15]. All charges were confirmed with other primary studies [16], and when available, with published cost ranges through the Oncofertility Consortium (oncofertility.msu.edu), Livestrong Foundation (livestrong.org), Attain Fertility (attainfertility.com), Cost Helper Health (health.costhelper.…”
Section: Cost Estimatesmentioning
confidence: 99%